Breaking the Barrier: Understanding Women’s Perceptions and Knowledge of Contraceptive Methods - Mohammad Mustafa Farooq Khan, Nosheen Zafar, Kinza Sohail, Mahnoor Jathol, Muhammad Talha Mumtaz, Gul Bibi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective; to identify barriers that prevents to access contraception among female Secondary objective was to determine the sources of awareness that can improve access to and use of family planning services. Methodology; A Cross sectional survey was carried out on in Public and private gynecological setups of Lahore. Sample of 300 women, focuses on family planning among women aged 18 to 45 in Lahore, were surveyed from January to May 2022. Categorical data was presented in the form of frequency and percentages and graphs. Results: Among the subjects 128(42.67%) were using Oral contraceptives, 85(28.33%) were using Condoms, 39(13%) were using Intrauterine Devices (IUDs), 28(9.33%) were using Injectable Contraceptives, 14(4.67%) had used Emergency Contraception and only 6( 2%) have Implants. On inquiring regarding source of information 184(61.30%) replied from Healthcare Provider, 72(24%) received from Friends / Family, 26(8.70%) get information from Media (TV/ Radio), 17(5.70%) learn from Internet and 1(0.30%) has other source of information. Among the barriers in using contraceptives 155(51.70%) replied Lack of awareness, 92(30.70%) replied Cultural/ religious beliefs, 44(14.70%) replied Lack of healthcare facilities, 25(8.30%) replied Fear of side effects and 20(6.70%) replied Cost of Contraception Conclusion: The study found that although many women are interested in using various contraception methods, several barriers exist that prevent them from accessing and using these services. The primary barriers include lack of knowledge, cultural and religious beliefs, limited access to healthcare facilities, fear of side effects, and contraception costs. Keywords: Contraceptive Methods, Knowledge, Women, Barriers